Urgensi Estetika dan Budaya Islam Dalam Pendidikan Agama Islam - Muslim, Asbullah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Palapa Nusantara Lombok NTB, 2013)
Education is one of culture process, there for education is canât be separated from culture and society. Integrating art and cultural values in education, especially Islamic education, will support the education goal in building studentâs personality, i.e.students who are independent, self confidence and possess inner brilliance. Through the experience in appreciating art works and cultural celebration, for example, it is expected that the student will sharpen their feelings and strengthen their personalities. Especially for teachers, they need the art values and tricks to manage their class and presentation, cause teaching is art. On the other hand, Islamic education plays the most important role in enlightening and revitalizing Islamic cultural values which will build up Islamic civilization in the future. Through Islamic education the students can be persuaded that on their hands the future of Islamic art and culture. More over, from Islamic education the lack and art/culture crisis will be solved by Islamic and spiritual values involvement in creating art and culture works